Innovative strategies to strengthen geriatric healthcare in India: bridging gaps through digital health and community-based interventions - Pritish Dhal; Subhashree Das; Lisa Sarangi (International Journal Of Community Medicine And Public Health, 2026)
India is experiencing a demographic shift with a rapidly growing elderly population projected to reach 20% by 2050. However, geriatric healthcare remains underdeveloped and inadequately integrated within the public health system. This article explores the status of elderly healthcare in India, highlighting key gaps in infrastructure, trained human resources, and service delivery. The National Programme for Health Care of the Elderly (NPHCE), though well-intentioned, suffers from limited implementation, particularly in rural and remote areas. The article examines the potential of digital health technologies such as telemedicine, mobile health units, and smart health monitoring to enhance access and continuity of care. Community-based approaches, including home visits by frontline health workers and family caregiver training, are presented as practical strategies to strengthen geriatric care. In addition, the psychosocial needs of the elderly mental health, family support, and palliative care are addressed as integral components of healthy ageing. The paper concludes by recommending a multi-sectoral approach involving policy integration, public-private partnerships, and targeted capacity building. Bridging the gap in geriatric care is essential not only for health equity but also for achieving India’s Sustainable Development Goals (SDGs), especially SDG 3, 9, and 17.